2010
DOI: 10.1002/agr.20262
|View full text |Cite
|
Sign up to set email alerts
|

Demand for value-added pork in Sweden: a latent class model approach

Abstract: A choice experiment survey dataset is used to investigate heterogeneous preferences among Swedish consumers for attributes of pig production. To model the preferences, a random parameter logit model and a latent class model are estimated and compared. The comparison, based on predicted probability distribution, regression analysis of the probabilities, and investigation of the probability ratio, suggests that the latent class model is preferred to the random parameter logit model. Estimating a latent class mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In other words, within each segment, consumer preferences are homogeneous but preferences vary between segments, reflecting a "lumpy" spread of preferences (Hynes et al, 2008). This modelling approach has also been used to better understand consumer preferences for agricultural products by identifying distinct valuation and behaviour patterns for each market segment (Hu et al, 2004;Kontoleon and Yabe, 2006;Nilsson et al, 2006;Cortiñas et al, 2007;Liljenstolpe, 2011). We use the latent class model as we anticipate differing valuation patterns, which may result in a differentiated marketing strategy according to consumer segments.…”
Section: Model Specificationmentioning
confidence: 99%
“…In other words, within each segment, consumer preferences are homogeneous but preferences vary between segments, reflecting a "lumpy" spread of preferences (Hynes et al, 2008). This modelling approach has also been used to better understand consumer preferences for agricultural products by identifying distinct valuation and behaviour patterns for each market segment (Hu et al, 2004;Kontoleon and Yabe, 2006;Nilsson et al, 2006;Cortiñas et al, 2007;Liljenstolpe, 2011). We use the latent class model as we anticipate differing valuation patterns, which may result in a differentiated marketing strategy according to consumer segments.…”
Section: Model Specificationmentioning
confidence: 99%
“…The studies relating to organic foods consumption reveal that consumers perceive organic foods to be healthier and safer (Magnusson et al., ; Lea & Worsley, ; Liljenstolpe, ; Shepard et al., 2005; Michaelidou & Hassan, ; Hoefkens et al., ). This dimension evokes an understanding that consumers may see some utilitarian benefits in organic food consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This makes biosecurity measures, like cleaning and disinfection of transport vehicles, important actions towards more sustainable food production [34]. In addition, animal transport is related to animal welfare issues, and increased use of mobile abattoirs and improved animal loading protocols (e.g., using loading docks) can reduce animal stress and improve welfare [35][36][37].…”
Section: Transport and Localizationmentioning
confidence: 99%
“…Labelling of sustainable food is a way of communicating sustainability through packaging and marketing. Several studies have demonstrated that Swedish consumers generally are positive towards climate labelling [93,97], and show a willingness to pay more for locally sourced food or food produced with more regard taken to climate, environment, and animal welfare [35,36,98], thereby potentially increasing demand for these products [97]. However, results also indicate an inconsistency in willingness to pay between consumers [36].…”
Section: Marketing Labelling and Consumption Of Sustainable Foodmentioning
confidence: 99%
See 1 more Smart Citation